Haemophilus influenzae Type b Meningitis in the Short Period after Vaccination: A Reminder of the Phenomenon of Apparent Vaccine Failure - Noa Greenberg-Kushnir; Orly Haskin; Havatzelet Yarden-Bilavsky; Jacob Amir; Efraim Bilavsky (Case Reports in Infectious Diseases)
We present two cases of bacterial meningitis caused by Haemophilus influenzae type b (Hib) which developed a few days after conjugate Hib vaccination. This phenomenon of postimmunization provocative time period is reviewed and discussed. These cases serve as a reminder to clinicians of the risk, albeit rare, of invasive Hib disease in the short period after successful immunization.